Official correspondence and papers regarding housing, - Ó Ceallaigh, Seán T. (Seán Tomás), 1882-1966 (1931)
Includes papers on the Housing (Financial and Miscellaneous Provisions) Bill, such as a speech by Ó Ceallaigh while he was Minister for Local Government and Public Health. Also includes newspaper cuttings on the Housing Bill and an article on the housing problem in The Watchword, June 4, 1932.